Comparison Of Criminal Sanctions Against Sexual Harassers In Indonesia And Malaysia - Satar, Abdul; Surnada, Surnada; Sitompul, Ariman (Legalpreneur Journal, 2024)
State on sexual harassment. This article uses normative research methods with a legislative approach and a comparative approach to the laws of Indonesia and Malaysia. Based on the results of the analysis conducted by the state of Indonesia and Malaysia have similarities in defining sexual harassment. Sexual harassment is part of sexual violence in the form of sexual acts through physical and non-physical touch with the target sexual organs or sexuality of the victim. Sexual harassment through physical touch in the form of poking or touching parts of the body. Sexual harassment in Indonesia is regulated by Law Number 12 of 2022 concerning the crime of sexual violence, while the criminal law on sexual harassment in Malaysia is regulated by the Anti-Sexual Harassment Law 2022. The threat of punishment for perpetrators of sexual violence in Indonesia is the highest 12 (twelve years) and/ or a maximum fine of Rp300, 000, 000.00 (three hundred million rupiah). While the threat of punishment for perpetrators of sexual violence in Malaysia is the highest 10 years or a fine or both.